Heteroannulated acceptors based on benzothiadiazole. Issue 1 (6th August 2014) - Parker, Timothy C.; Patel, Dinesh G. (Dan); Moudgil, Karttikay; Barlow, Stephen; Risko, Chad; Brédas, Jean-Luc; Reynolds, John R.; Marder, Seth R.
Abstract : Heteroannulated benzothiadizole acceptors in donor–acceptor polymers. Abstract : Increasing the acceptor strength of the widely used acceptor benzothiadiazole (BT) by extending the heterocyclic core is a promising strategy for developing new and stronger acceptors for materials in organic electronics and photonics. In recent years, such heteroannulated BT acceptors have been incorporated into a wide variety of materials that have been used in organic electronic and photonic devices. This review critically assesses the properties of these materials. Although heteroannulation to form acceptors, such as benzo[1, 2- c :4, 5- c ′]bis[1, 2, 5]thiadiazole (BBT), does result in materials with significantly higher electron affinity (EA) relative to BT, in many cases the extended BT systems also exhibit lower ionization energy (IE) than BT. Both the significantly higher EA and lower IE limit the efficacy of these materials in applications such as bulk heterojunction organic photovoltaics (BHJ-OPV) based on C60 . Although the relatively high EA may enable some applications such as air stable organic field effect transistors (OFET), more widespread use of heteroannulated BT acceptors will likely require the ability to moderate or retain the high EA while increasing IE.